2020
DOI: 10.9734/mrji/2019/v29i630184
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Faba Bean Production in Saltaffected Soils by Rhizobium leguminosarum bv. viciae Inoculation and Phosphorus Application

Abstract: Faba bean (Vicia faba L.) represents a major source of protein for animal and human nutrition, and provides several benefits such as improved soil quality. The Giza cultivar 87 (Vicia faba L.) was evaluated in three different salinity levels (6.9, 8.7 and 14.8 dSm-1) during two successive cropping seasons (2016-2017 and 2017-2018). The experiment was designed to analyze effect of soil salinity on nitrogen fixation, protein, chemical composition and crop productivity (for both grain and straw). Three phosphorus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The pH analyses indicated that the pH values of soil samples were 6.5 and 7.42 recorded from the Shentia and Dabat sites, respectively. Slightly acidic soil was noted with Shentia soil, and slightly neutral soil for Dabat soil (11) . Similarly, electrical conductivity (EC) analysis showed that soil samples have significantly different electrical conductivity, with the highest value of 0.094 obtained from the Dabat and a lower value of 0.073 obtained from the Shentia soil sample.…”
Section: Soil Analysismentioning
confidence: 96%
“…The pH analyses indicated that the pH values of soil samples were 6.5 and 7.42 recorded from the Shentia and Dabat sites, respectively. Slightly acidic soil was noted with Shentia soil, and slightly neutral soil for Dabat soil (11) . Similarly, electrical conductivity (EC) analysis showed that soil samples have significantly different electrical conductivity, with the highest value of 0.094 obtained from the Dabat and a lower value of 0.073 obtained from the Shentia soil sample.…”
Section: Soil Analysismentioning
confidence: 96%
“…Effect of Salinity levels on root length of broad bean varieties. The results of Table (7) indicate the existence of significant effects between the genotypes of beans and salinity levels in the characteristic of the dry weight of the root total (g), the Turkish variety significantly outperformed the rest of the Genotypes , as it achieved the highest average dry weight of the root total amounted to 14.06 (g) compared to the Dutch variety, which achieved the lowest average dry weight of the root total amounted to 8.62 (g). The reason for the increase may be due to the ability of the variety to benefit from the compounds in the rhizospheric region and invest them efficiently in increasing the activity of enzymes and hormones responsible for growth and thus better development of the root system.…”
Section: Root Length (Cm)mentioning
confidence: 99%
“…Many studies have been conducted on the effects of salt stress on the vegetative growth indicators of the bean plant, and the results of these studies have indicated that salinity greatly affects these indicators. [7] In her study carried out to evaluate the Giza 87 variety in three different levels of salinity (6.9, 8.7 and 14.8 ds/m) during two consecutive agricultural seasons (2016-2017 and 2017-2018), it was explained that salinity significantly reduced the vegetative growth indicators, as the high saline levels (14.8 dS/m) achieved the lowest average plant height of 31.33 cm and the number of branches reached 2.33 plant branches -1 , while the saline level (6.9dS/m) achieved the highest average of these characteristics of 92.33 cm and 4 plant branches -1 On the sequence. As noted [8].…”
Section: Introduction Broad Beanmentioning
confidence: 99%